2023
DOI: 10.1109/access.2023.3236006
|View full text |Cite
|
Sign up to set email alerts
|

Improved Particle Swarm Optimization for Laser Cutting Path Planning

Abstract: This research focuses on the long empty cutting path problem during the laser cutting process by employing an improved proximity method to establish the starting point set in complex closed graphics. Specifically, this work improves the particle swarm algorithm and proposes the Levy Flight, power function, and Singer map employed particle swarm optimization (LPSPSO) to avoid the disadvantages of the standard particle swarm optimization (PSO) algorithm. Specifically, the comprehensive prospect-regret theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Fei et al [23] introduced the update strategy of the HBA mining stage to enhance the global exploration ability, and used the disturbance operator and Levy flight strategy to disturb the ability of population individuals to jump out of local areas, aiming at the problem of slow convergence speed and easy local optimization of Sparrow algorithm. Qu et al [24] used Singer mapping to generate the initial population of PSO to enhance diversity, and introduced the Levy flight method to make it obtain the ability to jump out of local areas. Hou et al [25] promoted the diversity of the grey wolf population through Tent mapping, and used the nonlinear convergence factor based on the Gaussian distribution change curve to balance the search stage.…”
Section: ) Improved Version Of Swarm Intelligence Algorithmmentioning
confidence: 99%
“…Fei et al [23] introduced the update strategy of the HBA mining stage to enhance the global exploration ability, and used the disturbance operator and Levy flight strategy to disturb the ability of population individuals to jump out of local areas, aiming at the problem of slow convergence speed and easy local optimization of Sparrow algorithm. Qu et al [24] used Singer mapping to generate the initial population of PSO to enhance diversity, and introduced the Levy flight method to make it obtain the ability to jump out of local areas. Hou et al [25] promoted the diversity of the grey wolf population through Tent mapping, and used the nonlinear convergence factor based on the Gaussian distribution change curve to balance the search stage.…”
Section: ) Improved Version Of Swarm Intelligence Algorithmmentioning
confidence: 99%
“…Therefore, strategies must minimize the length of unnecessary laser head movements. This situation can also be considered an "empty trip" problem in laser cutting [11].…”
Section: The Laser Cutting Path Problem (Lcpp)mentioning
confidence: 99%
“…It is a typical representative of chaotic mapping and is widely used for the initial population generation of metaheuristic algorithms because of its traversal and non-repetitive characteristics. Additionally, Qu and Du[28] showed that Singer mappings' traversal uniformity and convergence speed are ideal for chaotic population initialization, and they experimentally proved that SingerVOLUME 11, 2023…”
mentioning
confidence: 99%